Bancada experimental para ensaios em geradores elétricos utilizados em aerogeradores de pequeno porte - AZEVEDO, Thiago Paula Silva de (Universidade Federal do Pará, 2012)
This dissertation presents a test setup for electrical generators used in small wind turbines. The system is basically composed by an induction motor, which simulates a wind rotor, mechanically coupled to the electrical generator under test; a frequency inverter, used to change the motor speed; transducers of electrical parameters, for the measurement of the parameters of interest (instantaneous voltage and current) at the generator output; an angular velocity sensor for measuring the rotation of the motor shaft; a microcomputer, for monitoring and storing the measured parameters, and control the frequency inverter, through a software developed; a data acquisition board, which serves as the interface between the transducers/sensor and the microcomputer. The angular speed supplied to the generator can be varied according to the given wind speeds values, which are associated with corresponding values of rotation, in order to simulate the behavior of a wind rotor. Thus, it is possible to trace the power curve (power versus wind speed) of the tested generator and analyze its performance. Also presented in this work are the results of measurements made, using the developed setup of a small commercial generator (1 kW) and other developed in a research project, both axial flux permanent magnet machines.